2018
DOI: 10.5964/ejop.v14i4.1592
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, social comparison, and Facebook use

Abstract: Facebook use is very popular among young people, but many open issues remain regarding the individual traits that are antecedents of different behaviours enacted online. This study aimed to investigate whether the relationship between self-esteem and the amount of time on Facebook could be mediated by a tendency towards social comparison. Moreover, three different modalities of Facebook use were distinguished, i.e., social interaction, simulation, and search for relations. Because of gender differences in tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 40 publications
2
49
1
Order By: Relevance
“…Adolescent with low self-esteem interested in social comparison, which related to greater amount of time spent on Facebook, searching information about others. They tend to make social comparisons to simulate different selfimage from reality and anxious about the response of their posts in total of likes or retweets in social media [11]. In this study self-esteem and social media wasn't related which might due to different types of social media.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Adolescent with low self-esteem interested in social comparison, which related to greater amount of time spent on Facebook, searching information about others. They tend to make social comparisons to simulate different selfimage from reality and anxious about the response of their posts in total of likes or retweets in social media [11]. In this study self-esteem and social media wasn't related which might due to different types of social media.…”
Section: Discussionmentioning
confidence: 75%
“…Level of self-esteem is influenced by treatment received from significant person especially parents and their respond to failure or success in achievement [5]. Other factors that also contribute to self-esteem are parenting styles [6], socioeconomic status [7], parents' education level [8], gender [9], genetic [10], social media [11], psychiatric disorders and chronic diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Third-party applications often appear in the form of quizzes, games, character reading, who I am in the future, even photo editing that tempt users to click on a user license agreement (Kozlowska, 2018). Activities of the younger generation like the most today are related to self-actualization on social media (Bergagna & Tartaglia, 2018) and they tend to trust product based on visual appearance (Permatasari & Kartikowati, 2018). Based on these observations, the respondents do not understand well the risks when entering their personal data into third-party applications.…”
Section: Resultsmentioning
confidence: 99%
“…This form of social comparison has been consistently described as a risk factor for negative mental health outcomes. [34][35][36][37] In addition, "envy" was also coded more frequently in the responses of our LGB participants. Previous research found that jealousy and envy on SM may behave as potential mediators in the relationship between SM use and negative mental health outcomes.…”
Section: Resultsmentioning
confidence: 99%